1987
DOI: 10.1037/0022-0663.79.4.409
|View full text |Cite
|
Sign up to set email alerts
|

Mothers' beliefs about the role of ability and effort in school learning.

Abstract: We studied the achievement goals of mothers in relation to their interpretation of school success, preferences for certain types of school feedback, task choices, causal attributions, and valuing of certain personal characteristics in their children. Over 500 mothers of children in kindergarten through fifth grade were surveyed. Mothers' preferences for mastery versus performance-based achievement goals were differentiated in terms of the priority mothers gave to the demonstration of effort versus high perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
145
2
3

Year Published

1988
1988
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 219 publications
(155 citation statements)
references
References 26 publications
5
145
2
3
Order By: Relevance
“…On 5-point scales (1 = not likely at all; 5 = very likely), students were asked to indicate the likelihood of their choosing two types of projects for that class. The items adapted from Elliott and Dweck's (1988; see also Ames & Archer, 1987) items were (a) "a project where you can learn a lot of new things but will also have some difficulty and make many mistakes" and (b) "a project that would involve a minimum of struggle or confusion and you would probably do very well." The items were conceptually similar, and students' responses to the two items were highly correlated (r = -.61, p < .001).…”
Section: Instrumentsmentioning
confidence: 99%
See 2 more Smart Citations
“…On 5-point scales (1 = not likely at all; 5 = very likely), students were asked to indicate the likelihood of their choosing two types of projects for that class. The items adapted from Elliott and Dweck's (1988; see also Ames & Archer, 1987) items were (a) "a project where you can learn a lot of new things but will also have some difficulty and make many mistakes" and (b) "a project that would involve a minimum of struggle or confusion and you would probably do very well." The items were conceptually similar, and students' responses to the two items were highly correlated (r = -.61, p < .001).…”
Section: Instrumentsmentioning
confidence: 99%
“…Even students in the same classroom may differ in the degree to which they focus on certain cues, as well as how they interpret them (Brattesani, Weinstein, & Marshall, 1984;Ryan & Grolnick, 1986). These individual differences may result from home influences (Ames & Archer, 1987;Parsons, Adler, & Kaczala, 1982), prior experiences (Stipek & Hoffman, 1980), or differential treatment by teachers (Marshall & Weinstein, 1986;R. S. Weinstein & Middlestadt, 1979).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Most families want their children to be successful in school, and ample evidence documents that parental involvement in school is associated with positive school outcomes (Ames & Archer, 1987;Grolnick et al, 1997;Hill & Craft, 2003;Luster & McAdoo, 1996). Few studies in developing countries have addressed this issue, however.…”
Section: Family and Community Impact On Student Learningmentioning
confidence: 99%
“…In general, research has identified two differentiated goals with mastery and performance goals (Dweck, 1986;Dweck and Leggett, 1988;Elliot and Dweck, 1988) or mastery and performance goals (Ames and Archer, 1987;Harackiewicz and Elliot, 1993) or task-involvement and ego-involvement goals (Nicholls, 1984). Mastery and performance goal orientation have different effects on performance, motivation, and affect.…”
Section: Introductionmentioning
confidence: 99%